Caracterização da reologia no estado fresco de pastas de cimento Portland fabricadas com nanotubos de carbono sintetizados diretamente sobre o clínquer - Paloma de Assis Soares (2019)
The search for concrete structures with high performance in terms of mechanical strength and durability has been the target of extensive research of the construction industry. In this context, the use of nanomaterials in traditional cementitious composites has attracted more attention in recent years, mainly because of some properties of these materials can be enhanced with the appropriate concentration and dispersion of carbon nanotubes (CNT) and carbon nanofibers (CNF). Understanding how the incorporation of these nanomaterials can modify the properties of cementitious pastes has important implications, since their impact on rheological properties, either right after mixing and during the initial time of hydration can affect mechanical strength and durability. However, it has been reported in the literature that the rheological properties of nanostructured cementitious composites have changed their workability. In this scenario, the aim of this investigation was to evaluate the rheological behavior of fresh pastes produced with different types of Portland cement manufactured with CNT/CNF synthesized directly on clinker. The mini-slump of Kantro and rotational flow rheometry were applied in this evaluation. Rheological tests were performed 30, 60 and 90 min after mixing in pastes produced with Portland cements CPIII-40 RS, CPV-ARI and Class G. The CNT/CNF content was 0.15% and 0.30% with respect to cement content. No chemical admixtures were used to disperse the NTC. The water/cement ratio varied between 0.4 and 0.5. The rheological behavior was adjusted to Bingham and modified Bingham mathematical models. For a water/cement ratios greater than 0.4, the results indicated no changes in rheological behavior of pastes containing CNT, regardless of the cement type and CNT content. The results also reveal a good correlation of fresh nanostructured cement paste rheological behavior in over time